POREDBENO-INTERKULTURNI ASPEKTI KNJIŽEVNE MAKEDONISTIKE U HRVATSKOJ (Filološke pripombe, 2019)
With its particular contrastive interest, literary-comparative and intercultural aspects of Croatian and Macedonian literature is pointed out as literatures of two mutually non-conflictive cultures and nations. Extracting literary-comparative as- pects of Croatian and Macedonian literature, as well as intercultural aspects of their histories of literature (especially the Macedonian literature in Croatia), this paper is analyzing the specific attitude of Croatian South Slavic's towards Macedonian literature, regarding on reputable historians of literature of the newer generation (Goran Kalogjera and Borislav Pavlovski).